Depiction of Nidi and Fibrovascular Zones of Osteoid Osteomas Using Gamma-Correction Tc-99m HDP Pinhole Bone Scan and Conventional Radiograph, and Correlation with CT, MRI, and PVC Phantom Imaging - Bahk, Yong-Whee; Kim, Sung Hoon; Chung, Yong-An; Bahk, Won-Jong; Park, Jung Mee; Kang, You Mee; Choi, Woo Hee; Park, Young Ha; Sohn, Hyung Sun; Kim, Byung Ki; Chung, Soo Kyo (Nuclear medicine and molecular imaging, 2011)
Purpose For the precise imaging diagnosis of osteoid osteoma (OO), the identification of the nidus and fibrovascular zone (FVZ) is essential. However, the latter sign has received little attention because it is difficult to demonstrate. We applied the recently introduced gamma correction (GC) to depict the FVZ on pinhole bone scan (PBS), conventional radiography (CR), and computed tomography (CT). Non-gamma correction MRI was also analyzed for reference. Methods Ten patients with histologically proven diagnoses of OO were enrolled in this retrospective study. PBS, CR, and CT were processed by GC to demonstrate the nidi and FVZ as distinct yet integrating components of OO. PBS was performed using a 4-mm pinhole collimator 3 h after iv injection of 925 to 1,110 MBq (25 to 30 mCi) of Tc-99m HDP, and anteroposterior and mediolateral CR and transverse CT were taken according to the standard technique. MRI sequences included T1- and T2-weighted images. For gamma correction, we utilized the Photo Correction Wizard program of ACD Photo Editor v3.1. A team of three qualified nuclear physician-radiologists, two nuclear physicians, and one MRI specialist read bone scans, radiographs, and MRIs of OO according to each specialty, and orthopaedic aspects and histology were reviewed by one qualified orthopedic surgeon and two qualified pathologists, respectively. Each observer first read the images separately with basic information about the aim of the study given and then in concert. Interpretive disagreement was settled by discussion and consensus. Results On pinhole scan, nidi were presented as areas of intense tracer uptake in all cases, and, importantly after GC, a thin ring-like zone with lower tracer uptake became visible in seven out of ten cases. GCCR also revealed a thin lucent zone that circumscribed the nidi in six out of ten cases and GCCT in two of four cases. MRI, without GC, presented nidi with high signal in the center and a thin ring-like zone with low signal in the periphery in five out of six cases. Ring-like zones were 1–2 mm in thickness and circumscribed the nidus as an integrated part and, hence, were morphologically interpreted as FVZ. Histologically, the presence of a variously mineralized FVZ was confirmed in four cases, but individual locus-by-locus image-histology correlation could not be accompolished because specimens were fragmentary. In the FVZ, tracer uptake was lower than in nidi, presumably reflecting that bone metabolism in the two parts differs as in their histology. Statistically, no significant correlation existed between the duration of symptoms and imaging demonstrability of the FVZ (Spearman’s test r = −0.057, p = 0.877), but parallelism existed in the demonstrability of the FVZ among GC PBS, CR, and CT, and non-correction MRI. Conclusions GC was useful to enhance the resolution of PBS, CR, and CT in OO so that both the nidi and FVZ were separately imaged. The use of CG PBS and CR in combination is recommended for the specific diagnosis of OO with information about bone metabolism and anatomical characteristics. PBS and CR are economical and widely available.